(untitled) (International journal of artificial intelligence, 2026)
Growth and development in childhood are complex processes regulated by genetic, nutritional, and hormonal factors. Endocrine disorders represent one of the most important causes of growth disturbances and developmental abnormalities in pediatric populations. This study analyzes growth and developmental characteristics of children with endocrine pathology in the Andijan region. Anthropometric indicators, including body height, body weight, and body mass index, were assessed, and developmental deviations associated with various endocrine disorders were evaluated. The findings indicate that children with endocrine pathology demonstrate significant growth and developmental impairments compared to age-related normative standards. Early diagnosis and comprehensive management are essential for improving growth outcomes and overall health in affected children.